Family Guidance in Efforts to Handle Middle Adult Women Who Decide to Postpone Marriage - Awalia, Awalia; Siti Khotijah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In this increasingly modern era, there are still women who decide to postpone marriage in order to pursue a career, continue their education, or become the backbone of the family and have not yet found the right partner. In this case, the family has an important role in providing guidance to women who decide to postpone marriage, namely in the form of advice and motivation about family life. In this case, family guidance is one strategy that can be used to deal with women who decide to postpone marriage in Pragaan Laok Village. The problems raised in this research are 1) What are the factors that cause middle-aged women to decide to postpone marriage in Dunglaok Hamlet, Pragaan Laok Village, Pragaan District, Sumenep Regency and 2) What is the family guidance model in an effort to handle middle-aged women who decide to postpone marriage in Dunglaok Hamlet, Pragaan Laok Village, Pragaan District, Sumenep. The approach in this research uses a qualitative approach with a case study type. The method used is observation and interviews. The informants in this study were 3 people who were family members and 4 women who decided to postpone their marriage. The validity of the data in this research is triangulation, namely triangulation of sources and techniques. The results of this research are: First, the factors that cause middle-aged women to decide to postpone marriage are wanting to be the backbone of the family, focusing on continuing their education at a higher level, focusing on a career so they can be independent and make their parents happy. And the second is a model of family guidance in an effort to deal with middle-aged women who decide to postpone marriage, namely providing advice on how to be a good wife and how to build a Sakinah Mawaddah Warahmah family and providing motivation that marriage is a complement to religion and morals.